Pendekatan Teori Akuntansi Positif Dalam Kasus Derivatif PT Telekomunikasi Selular - Syalwa Naira Eka Putri; Rizki Aisyah Marpaung; Paradilla Sandi Br Bangun (FEB Universitas Maritim Semarang, 2024)
Telkomsel is the leading provider of cellular telecommunications services in Indonesia based on market share. At the end of March 2008, Telkomsel had 51.3 million subscribers, which based on industry statistics represents an estimated market share of almost 51%. Telkomsel provides GSM cellular services in Indonesia, nationally via the dual band GSM network 900/1800 MHz and internationally via 288 international roaming partners in 155 countries (at the end of 2007. The aim of this research is to analyze the company's condition by looking at the financial ratios that describe company performance and analysis of the company's optimal capital structure. The data in this research is secondary data originating from the Central Statistics Agency, the Agency for the Application and Assessment of Technology, the Directorate General of Posts and Telecommunications and the Directorate General of Telematics Applications, Department of Communications and Information Technology. Data used in This research is data about the condition of the cellular telecommunications industry in Indonesia which includes expenditure, infrastructure, customers, human resources (labor). Data was taken from company condition reports (annual reports) PT. Telkomsel, PT. Indosat , and PT Excelcomindo for the quarterly period 2005-2008.